High efficiency differential chaos shift keying modulation scheme without intra-signal interference - Hua YANG; Guo-ping JIANG; Jun-yi DUAN (Tongxin xuebao)
To eliminate the adverse effect brought by the intra-signal interference components in decision variables in high efficiency differential chaos shift keying system,a novel high efficiency differential chaos shift keying modulation scheme without intra-signal interference was proposed.By changing signal format of the chaotic carriers,the proposed scheme makes the two modulated chaotic signals transmitted in same time slot strictly orthogonal,which removes all possible intra-signal interference components from all decision variables clearly.It is shown by the analysis and simulation results that the proposed system has much better performance than HE-DCSK.